Piperine pretreatment attenuates renal ischemia-reperfusion induced liver injury - Mohammadi, Maryam (Heliyon, 2019)
BACKGROUND: Remote organ injury is one of the complications which are developed following ischemia-reperfusion induced acute kidney injury (AKI), dramatically increasing its mortality rate. The aim of the present study was to investigate the effect of piperine pretreatment on liver dysfunction following ischemia-reperfusion induced AKI. MATERIALS AND METHODS: Acute kidney injury was induced by 30 min-bilateral renal ischemia followed by 24 h of reperfusion. To investigate liver damages, the levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) enzymes were measured in plasma. In order to study oxidative stress, malondialdehyde (MDA) and ferric reducing antioxidant power (FRAP) levels were measured. Furthermore, the expression of intercellular adhesion molecule-1 (ICAM-1) mRNA along with infiltration of leukocytes in the liver tissue was measured for inflammation assessment. Histopathological damages were studied through measuring the extent of cellular fibrosis, sinusoidal dilatation, and vascular congestion in liver tissue. RESULTS: Following acute kidney injury, AST, ALT, and ALP levels in plasma, MDA level and ICAM-1 expression in the liver tissue, infiltration of leukocytes into the interstitium, and hepatic histopathologic damages increased significantly, while FRAP decreased. Pretreatment with piperine at 10 and 20 mg/kg body weight was able to improve these damages, such that some of them reached its value in the sham group, though piperine in the 20 mg/kg was more effective. CONCLUSIONS: The results of this study suggest that ischemia-reperfusion induced AKI result in hepatic damages, and pretreatment with piperine can prevent development of these damages through its antioxidant and anti-inflammatory properties.